Access to health and support services: perspectives of people living with a long-term traumatic spinal cord injury in rural and urban areas. (July 2015) - Goodridge, Donna; Rogers, Marla; Klassen, Laura; Jeffery, Bonnie; Knox, Katherine; Rohatinsky, Noelle; Linassi, Gary
Abstract Purpose: To examine the perspectives of persons living with traumatic spinal cord injuries (tSCI) on their access to health and support services. The specific aims were to identify the perceived gaps in access, classify the nature of the perceived gaps and compare differences in perceptions of access between urban and rural participants. Method: Using a descriptive, qualitative approach, semi-structured interviews were conducted with 23 adults living with tSCI, 13 of whom had paraplegia. Ten participants resided in rural areas and 16 were male. Thematic analysis allowed for the identification of patterns, which were then categorized according to the dimensions of access. Results: Opportunities to engage in health-promoting activities through a broad range of health and support services were at times limited, particularly by issues of affordability. In addition to core healthcare services, participants reported the need for complementary therapies, sports and leisure, peer support, equipment and mobility related services. Availability and accessibility of services was limited in some cases for rural participants, although rural residence conferred other valued benefits. Narratives of "not being heard" by providers were common. Conclusions: Maintaining health and well-being in people with tSCI demands access to both conventional health care and support services. Implications for Rehabilitation Access to both health and support services are important to maintaining the health and wellness of people with spinal cord injury. People with spinal cord injuries take an active role in coordinating their health, at times assuming various roles to compensate for perceived shortcomings of health care providers. Negotiating balances of power with gatekeepers in the health and insurance sectors was a key function of the coordinating role assumed by people with spinal cord injury. In order to effectively address the needs of this population, a coordinated interdisciplinary out-reach service, which includes peer support, must cross boundaries to engage sectors beyond traditional health care services, such as insurers and wellness providers.